Trend of ambient air quality in Chittagong City - Rouf, MA; Nasiruddin, M; Hossain, AMS; Islam, MS (Bangladesh Journal of Scientific and Industrial Research, 2012)
The ambient air quality data for particulate matter as well as criteria of gaseous pollutants were collected during December 2006 to December 2008 at the Continuous Air Quality Monitoring Station (CAMS) located at TV center, Pahartoli, Chittagong. It was observed that during April- October, 24 hour average concentration of PM10 and PM2.5 were within the National Ambient Air Quality Standard (NAAQS) level but it increased occasionally by more than two and a half times during the whole non-monsoon period (November-March). The highest values found of PM2.5 were 327 ?g/m3 and 254.9 ?g/m3 24 hour average concentration in January 2007 and December 2008 respectively. Whether, the highest alarming concentration of PM10 was reported as 545 ?g/m3 in January 2007. The other gaseous pollutants such as SO2, NO2, O3, CO and hydrocarbons remain well within the permissible limit except dry winter. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13062 Bangladesh J. Sci. Ind. Res. 47(3), 287-296 2012